Private Label Consumption and Entrepreneurship in South Africa - Malgas, Juanita (My University, 2018)
ABSTRACT This paper highlights how the unemployed can capitalise on the growing trend of private label consumption. With high unemployment rate figures, coupled with poor economic growth there is a real need for the unemployed to establish businesses as a means of generating income. Trends in consumer behaviour signal that private labels are growing in popularity and are becoming more significant in a consumer’s basket (within retailers and wholesalers). Literature on entrepreneurship focuses on elements that entrepreneurs need to focus on such as marketing, accounting, and identifying opportunities, etc. This paper demonstrates that it is possible, albeit challenging in some instances, for hopeful entrepreneurs to become suppliers of private labels for retailers. These hopeful entrepreneurs need to make themselves known to retailers so that they are considered when a product is needed. This can be achieved through marketing but also by approaching retailers and asking what it is that they require and meeting their need by producing the required product. Data was collected from professionals who have exposure to private labels because they are either private label buyers or their companies manufacture private labels, entrepreneurs who make their own products and unemployed women or hopeful entrepreneurs as they will be referred to in this paper. This data was collected by way of interviews. Ultimately, the unemployed participating in the production of private labels is a viable alternative source of business which has not received much attention from leading entrepreneurship schools of thought. Entrepreneurship is one of the key elements for reducing unemployment levels in this country and it is of great importance that ideas such as the ones this paper will centre around are explored in order to achieve the countries employment goals. Black Economic Empowerment (BEE) was also considered in this paper because when analysing the country’s unemployment, it is important to be cognisant of the majority of the unemployed and they are black South Africans. What this paper reveals is that whilst the government requires companies to be BEE compliant, there are companies that do not consider BEE when choosing suppliers to work with.
Keywords: Keywords: Entrepreneurship, Unemployment, Private Label, Consumer Trends, Manufacturing, Retail, Black Economic Empowerment